(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
it is plentiful to use metaphor in politics because they used it to control the humans in their feelings, beliefs, ideas or values. There are many types of metaphors that politicians used to deliver their messages. As the figurative language deliver the direct meaning more than the literal meaning. This paper has a speech from the president Donald Trump who deal with the democrats and previous government as an enemies to the USA. He express many meanings to politics as; politics is love, politics is war, politics is crime, politics is friendship, politics is a journey or a race. Also he shows politics as a game, water, or a sleep. Evaluation use the same metaphor may differ in the connotation as positively or negatively (KTU, 2018). Many journalists analyze his speech patterns or pronunciation also his semantic space which connects between concepts. Republications like to refer progress with business while Democrats with welfare (Weisberg, August 2, 2017). So, here the paper explain in the first part, the metaphor definition and types. The second part explains the cognitive aspect of conceptual metaphor. The third part explain the the speech of Trump within the previous cognitive categories. This research wants to convey the preferable categories that is frequently used by the speaker. Key words—Metaphor, psycholinguistic, politics, evaluation, Trump, cognitiveit is plentiful to use metaphor in politics because they used it to control the humans in their feelings, beliefs, ideas or values. There are many types of metaphors that politicians used to deliver their messages. As the figurative language deliver the direct meaning more than the literal meaning. This paper has a speech from the president Donald Trump who deal with the democrats and previous government as an enemies to the USA. He express many meanings to politics as; politics is love, politics is war, politics is crime, politics is friendship, politics is a journey or a race. Also he shows politics as a game, water, or a sleep. Evaluation use the same metaphor may differ in the connotation as positively or negatively (KTU, 2018). Many journalists analyze his speech patterns or pronunciation also his semantic space which connects between concepts. Republications like to refer progress with business while Democrats with welfare (Weisberg, August 2, 2017). So, here the paper explain in the first part, the metaphor definition and types. The second part explains the cognitive aspect of conceptual metaphor. The third part explain the the speech of Trump within the previous cognitive categories. This research wants to convey the preferable categories that is frequently used by the speaker.